Influence of guava residue on tambaqui growth performance - Ubatã Corrêa Pereira; Nataly Meira Matos; Romy Gleyse Chagas Barros; Priscila Monise Dos Santos Santana; Anailton Carlos Alves de Almeida; Jodnes Sobreira Vieira; Carolina Nunes Costa Bomfim (Acta Scientiarum. Animal Sciences, 2022)
Fruit residues represent alternative ingredients that can be included in diets of tambaqui, Colossoma macropomum. This study evaluated the growth performance of tambaqui fed diets containing different levels of guava agroindustrial residue. The experiment was based on a completely randomised design, with 105 fish randomly distributed in 15 plastic 60 L-1 boxes with a water recirculation system. Feeding was carried out to apparent satiety for 45 days, using diets with 0, 50, 100, 150 and 200 g kg-1 inclusion of guava residue. Biometrics were performed every 15 days. Quadratic effect (p < 0.05) was observed for daily feed intake and apparent feed conversion, with optimum levels of 4.86 and 6.05% inclusion of guava residue, respectively. There was no significant difference (p > 0.05) in relation to final weight, weight gain, specific growth rate, hepato-somatic index, survival rate and protein efficiency rate by the dietary treatments. The inclusion of up to 150 g kg-1 of the guava agroindustrial residue in the feed did not compromise the performance of tambaqui juveniles.